2021
DOI: 10.1007/s11013-021-09762-1
|View full text |Cite
|
Sign up to set email alerts
|

What About Us? Experiences of Relatives Regarding Physician-Assisted Death for Patients Suffering from Mental Illness: A Qualitative Study

Abstract: Physician-assisted death (PAD) for patients suffering from mental illness is legally permitted in the Netherlands. Although patients’ relatives are not entrusted with a legal role, former research revealed that physicians take into account the patient’s social context and their well-being, in deciding whether or not to grant the request. However, these studies focussed on relatives’ experiences in the context of PAD concerning patients with somatic illness. To date, nothing is known on their experiences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Most studies were published in Canada (n=15) 6 23–36. Other jurisdictions included Switzerland (n=3),37–39 Netherlands (n=3),16 40 41 USA (n=2),42 43 Australia44 or multiple jurisdictions or not specified (n=4) 5 7 10 32 45. Of the 22 identified empirical studies, almost half employed exploratory qualitative methodology (n=13),23–26 28 30 31 33 34 36 37 43 44 with the remainder being either observational quantitative studies (n=6)29 38–40 42 44 or mixed-methods studies (n=3) 6 27 35.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were published in Canada (n=15) 6 23–36. Other jurisdictions included Switzerland (n=3),37–39 Netherlands (n=3),16 40 41 USA (n=2),42 43 Australia44 or multiple jurisdictions or not specified (n=4) 5 7 10 32 45. Of the 22 identified empirical studies, almost half employed exploratory qualitative methodology (n=13),23–26 28 30 31 33 34 36 37 43 44 with the remainder being either observational quantitative studies (n=6)29 38–40 42 44 or mixed-methods studies (n=3) 6 27 35.…”
Section: Resultsmentioning
confidence: 99%
“…There were five studies that included the perspectives of HCPs on a family/friend’s bereavement, with two studies30 33 including only physicians, nurses, case workers and social workers, and another study29 including only physicians. A few studies had specific research questions regarding a MAiD patient subpopulation or the setting of MAiD: Swarte et al 40 focused on MAiD within the context of patients with cancer; Hashemi et al 6 studied MAiD cases which took place at home; and Pronk et al 41 studied family/friends of patients with mental health in relation to MAiD. There were four studies34 35 40 42 that compared family/friend’s bereavements of those who received MAiD and those who did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, given that these euthanasia trajectories and their outcomes affect so many actors directly or indirectly involved, future focus group studies bringing both the patient population and the health care team, including the patients social inner circle, together, may elucidate how and to what extent one can address and meet other actors' needs. Particularly the perspective of patients' social inner circle is missing, while a Dutch study found a considerable role in and impact of the euthanasia trajectory for them ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is literature about MAiD examining caregivers and family relatives of patients with terminal somatic illness [34], there are only very few studies on families of patients with psychiatric disorders. A qualitative Dutch study showed that although the relatives of psychiatric patients were understanding of their wish to die (e.g., compassion, respect for autonomy, fear that the patient will commit a gruesome suicide), they also hoped that they would make another choice [35].…”
Section: Opinions and Attitudes Of Relatives Of Patients With Psychia...mentioning
confidence: 99%